Czy kapitalizm może być etyczny? - Kowalik, Tadeusz (Annales. Etyka w Życiu Gospodarczym, 2008)
It is the individualistic approach which prevails in previous analysis of the problem of ethics ineconomy. The problem of the ethical attitude concerns individuals, business people, managers,politicians and economists. The publications about business ethics lack analysis of systemcircumstances in which individuals and companies act. If capitalism is just the power of capital ownersover workers and if, according to Schumpeter, it is “the civilization of inequality and of the familyfortune”, than it can be easily judged as a system of predominantly unethical tendencies.Nevertheless, it is worth raising questions about ethical character of various types of capitalism.Participation capitalism is one which ensures (nearly) full employment, a social minimum wagefor everyone and the real power of society including workers’ participation in decision processes.The structural conditions of such capitalism force and even encourage ethical behaviour.The capitalism of the protective state was founded by J.M. Keynes, W. Beveridgeand Will Hutton with his stakeholder capitalism. Many European countries approach this standard ofcapitalism.Predacious capitalism (turbo-capitalism) is a maximum-profit-oriented capitalism with no regardto social costs. The nearest example is the post-Reagan American capitalism.Polish capitalism fails to pass muster even in regard to the liberal capitalism.